2021
DOI: 10.1002/ps.6414
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of alginate–chitosan floating granules loaded with 2‐methyl‐4‐chlorophenoxy acetic acid (MCPA) and their bioactivity on water hyacinth

Abstract: BACKGROUND Water hyacinth (Eichhornia crassipes) is considered the most damaging aquatic weed in many countries. Chemical methods are still the primary approach to control, although this directly exposes the natural enemy of water hyacinth (water hyacinth weevil) to herbicides. In addition, spray drift can easily damage non‐target plants. In this study, herbicides, natural polymer materials (chitosan and carboxymethyl chitosan), sodium alginate and natural oils (citronella oil) were used to prepare novel float… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The preparation method of drug-loaded particles was based on the procedure of Hou et al [ 39 ], and the influence of the controllable factors on drug loading was explored.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation method of drug-loaded particles was based on the procedure of Hou et al [ 39 ], and the influence of the controllable factors on drug loading was explored.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to their inherent potential pathogenicity towards plants, various fungal pathogens are found to be effective biocontrol agents for the water hyacinth. Till date, the most widely explored bioherbicides in the control of water hyacinth include A. alternata, Aspergillus niger, Fusarium, few species of Myrothecium and their metabolites [91,104]. The growth and environmental conditions for these potential isolates have been optimized at the laboratory scale; however, mass production is needed to meet the demand of actual applications.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
“…Recent expansion in this regard includes the use of carriers, granules and emulsions as formulations for the effective delivery of bioherbicides. Hou et al [104] reported the successful use of alginate granules encapsulated herbicide 2-methyl-4-chlorophenoxy acetic acid in the removal of water hyacinth plants. The floating granules themselves got collected in the vicinity of water hyacinth stems and roots thereby targeted the sustained release of herbicide [104].…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest for chitosan as a carrier of agrochemicals for slow or controlled release due to its biodegradability, non-toxicity, chemical modifiability, pH-responsiveness and abundant source. [20][21][22] Chitosan is obtained by deacetylation of chitin, a natural resource found widely in crustaceans of marine arthropods such as shrimp and crabs, cell membranes of fungi and algae, shells and bones of mollusks. Chitosan has the potential to adhere to surfaces owing to the presence of hydroxyl and amine groups, which also offers the possibility for chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%